Modern printing technology, problems of implementation and application in production (Herald of Journalism, 2020)
The full range of preparatory work, a prerequisite for rapid develop ment of industrial and organizational innovation, provides access to the optimum process parameters and leads to the achievement of the planned level of production efficiency.
Keywords: printing, innovative technology, publishing, manufactur ing, marketing, competitiveness, competence.